ASSESSING ADMINISTRATIVE STRATEGIES FOR ENHANCING PEACE EDUCATION IN JUNIOR SECONDARY SCHOOLS IN THE AGADEZ REGION, NIGER REPUBLIC - Cheffou, Idi (Sokoto Educational Review, 2015)
This study was carried out to assess administrative strategies for enhancing Peace Education (PE) in 29 Junior Secondary Schools in the region of Agadez, Niger Republic. The study was descriptive. Quantitative and non- parametric data that helped determine majority views were collected, tallied, converted into simple percentages and means using a calculator. Information from documents that were initially in French was translated into English. The research used a total population of 487 teachers and school administrators from 29 Junior Secondary Schools in the region of Agadez. All the 84 administrators from the 29 Junior Secondary Schools were included in the research as their number was small; 388 teachers were sampled out of 403 using the Research Advisors’ Sample Size Table and Simple Random Technique. The research instrument was a self-designed structured questionnaire titled Administrative Strategies for Enhancing Peace Education Questionnaire, which was validated and had a reliability index of .75. This paper dealt with the curriculum content that could enhance Peace Education in Junior Secondary Schools in the region of Agadez. The findings revealed that the Peace Education curriculum content was scanty. The study recommended, among others, that the Junior Secondary Schools Peace Education curriculum should be revised, and should therefore encompass relevant issues that would mould the students’ minds, issues that would help them to learn to live together and enhance mutual understanding in community; to this end, the Peace Education curriculum should mainstream Human Rights Education, Conflict Resolution Education, Disarmament Education, Development Education, International Education, Civics and any other type of education that is likely to bar the students from getting involved in violent conflict or even terrorism.